valuation of the Prevalence of Generalized Anxiety Disorder and Its Association with Worry in Students of Zanjan University of Medical Sciences - Alireza Rashtbari; Mohsen Dadashi; Mohammad Masoud Vakili; Hossein Malekizadeh (Zanjan University of Medical Sciences and Health Services, 2020)
Background and Objective: Generalized anxiety disorder (GAD) is one of the most prevalent psychiatric disorder, characterized by excessive worry and anxiety about different daily events and activities. The disorder causes severe problems in the academic and career performance of individuals. However, students are more prone to the damages of the disorder due to environmental and educational pressure. Therefore, this study aimed to evaluate the prevalence of GAD and its association with worry in students of Zanjan University of Medical Sciences, Zanjan, Iran. Materials and Methods: This cross-sectional research was performed on 350 students (66.2% female) in the academic year of 2018-2019, selected by the availability sampling method. Data were collected using the Penn State Worry Questionnaire (PSWQ) and Generalized Anxiety Disorder 7-item scale (GAD-7) to determine the level of worry and prevalence of GAD in the participants. Data analysis was performed in SPSS version 25 using Chi-square, Mann-Whitney U, and Kruskal-Wallis tests. Results: In this study, 20.6% of the participants met the criteria for GAD diagnosis. Also, the GAD prevalence was higher in female students, compared to the male participants. However, this difference was not statistically significant (P>0.05). Furthermore, there was a significant difference between the participants with GAD and healthy students regarding the worry score (P<0.05). Conclusion: According to the results of the study, a considerable number of students of Zanjan University of Medical Sciences suffered from GAD, which might have affected their academic performance. It is essential to conduct more comprehensive studies in this area and to provide psychological interventions aimed to reduce the GAD damages in students.